INTEGRATED ANTI-CRISIS HUMAN RESOURCE MANAGEMENT MODEL FOR UKRAINIAN ENTERPRISES IN WARTIME - OVCHARUK, Olekcandr; ONUSHKANYCH, Yaroslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the transformation of personnel management systems in Ukrainian enterprises under conditions of full-scale war, emphasizing the integration of sustainable development principles and resource optimization strategies. In prolonged military conflict, enterprises face unique challenges that differ significantly from short-term economic crises. Among the most critical challenges identified are severe personnel shortages caused by mass mobilization, migration, and internal displacement, which force organizations to compete for a limited pool of qualified employees. Additionally, chronic psychological and emotional exhaustion of employees emerges as a significant concern, significantly affecting productivity, increasing error rates, and exacerbating workforce turnover. The study also highlights transformations in labor relations, including changes in working hours, remuneration policies, and employment procedures, which necessitate careful balancing of organizational survival and employees’ social rights. Moreover, the destruction of infrastructure and disruptions to business processes, including frequent energy outages, require enterprises to adopt flexible operational schedules and optimize resource allocation while maintaining continuity of core activities. The article argues that effective adaptation to such extreme conditions demands a holistic and integrated approach to human resource management. Specifically, successful enterprises combine measures to preserve and develop human capital, provide comprehensive psychosocial support, implement green HR practices to optimize resource use, digitalize management processes for operational flexibility, and strengthen corporate social responsibility initiatives. It is empirically demonstrated that principles of sustainable development, including environmental and social responsibility, are not merely ethical considerations but serve as strategic tools that enhance organizational resilience and competitiveness. For example, green HR practices contribute to tangible cost savings, facilitate resource-efficient operations, and create conditions for attracting international investments and integrating into European supply chains.Based on the analysis of Ukrainian empirical cases, the study proposes an integrated model of crisis personnel management that aligns short-term survival strategies with long-term organizational sustainability under martial law. This model emphasizes the strategic role of top management in fostering a culture of resilience, adaptive competence development, digital transformation, and psychosocial well-being. It also highlights the importance of stakeholder engagement, including government support mechanisms and international donor assistance, to enhance human capital sustainability. Overall, the study contributes to developing new theoretical approaches to personnel management in extreme conditions, offering practical guidance for enterprises operating in war-affected environments and enriching global knowledge on organizational resilience and sustainable human resource management.
Keywords: crisis personnel management; sustainable development; resource optimization; organizational resilience; human capital